Synthesis and Binding Properties of a New Fluorescent Molecular Sensor Based on a Triazole Nucleoside. (October 2016) - Guo, Lijuan; Zhang, De-Hua; Duanyi-Ping,; Xiong, Ze-Shan; Liu, Yan
A new fluorescent nucleoside based on 1, 2, 4-triazole nucleoside has been synthesised and its X-ray structure determined. Its binding properties, investigated by fluorescence spectroscopy, show that it can selectively bind Hg 2+ with fluorescence quenching.